Investigasi Topik Riset Jasa Ekosistem dan Sistem Informasi Geografis Menggunakan Analisis Bibliometrik - Lahay, Rakhmat Jaya; Lihawa, Fitryane; Hasim, Hasim; Baderan, Dewi Wahyuni K; Mahmud, Marike; Mohamad, Nurdin (Jurnal Ilmu Alam dan Lingkungan, 2024)
Ecosystems play a role in ensuring human survival on earth, in the form of ecosystem services in the form of food, air, water and energy. One technique for assessing ecosystem services is by utilizing geospatial information technology. This paper explores the development of research into the assessment of ecosystem services using geospatial information technology. The investigation method utilizes VOSviewer software and bibliographic data which can be accessed for free from 2000 to 2024. Descriptive analysis and simple text analysis were applied to explain the appearance of certain topics in scientific articles. This study shows that the amount of geospatial information technology research for ecosystem services assessment fluctuates with an upward trend during 2000-2024. This study found 491 scientific articles, which were related to the keywords ecosystem services and geographic information systems. This article is distributed in 95 international journals, most of which are indexed by Scopus Q1. The simultaneous appearance of the keywords ecosystem services and geographic information systems is dominant in the two Scopus Q1 journals, namely Ecological Indicator and Ecosystem Services. Referring to the journal coverage categories, the dominant main subjects appearing are Environmental Science, Agricultural and Biological Sciences, and Social Sciences. This research found 25 main keywords grouped into 5 clusters. The use of geospatial information technology (RS and GIS) for ecosystem service assessment was found in 101 articles. Implementation of this technology is in the form of models, tools, platforms, devices, software, techniques and spatial analysis. The use of sensing data in the form of LiDAR, PolSAR, Landsat, Modis and Sentinel for monitoring ecosystem services also appeared in 69 articles. The results of this research are expected to provide the latest knowledge for stakeholders who focus on assessing ecosystem services.